Synthesis of some novel pyrazolo[3,4-d] pyrimidin-4(5H)-one derivatives as potential antimicrobial agent - Dipen K Sureja; Sandip P Dholakia; Kantilal R Vadalia (Wolters Kluwer Medknow Publications, 2016)
Objectives: The aim of the present work was to synthesize a novel series of pyrazolo[3,4-d]pyrimidin-4(5H)-one derivatives and evaluate their in vitro antimicrobial activity. Methods: Cyclization of an ortho-amino ester of 1-(2,4-dinitrophenyl)pyrazole with various aliphatic/aromatic nitriles under different reaction conditions such as conventional and microwave assisted synthesis, provided pyrazolo[3,4-d] pyrimidin-4(5H)-one derivatives. All the synthesized compounds were evaluated in vitro for their antimicrobial activity against selected bacteria and fungi by agar well diffusion method. Results: All newly synthesized compounds were characterized using spectral and elemental analysis. Compounds 2e, 2f, and 2g showed significant antimicrobial activity as compared to standard drugs used. Conclusion: The newly synthesized compounds could be useful templates for the design and optimization of more active analogs as a possible antimicrobial agent.